The importance of screening for critical and severe congenital cardiac diseases by pulse oximetry in the early neonatal age - Position statement of the Hellenic Society of Perinatal Medicine (HSPM) - Andreas C. Petropoulos; George Daskalakis; Fani Anatolitou; Makarios Eleftheriadis; Panos Antsaklis; Athina Moutafi; Panagiotis Petropoulos; Anastasia Varvarigou; Antonia Charitou (Hygeia Press di Corridori Marinella, 2021)
Background: From its first reported use in 2002, the efficiency of pulse oximetry (POX) screening in detecting critical and severe congenital heart disease (c/s-CHD) in term neonates in early days after delivery has been proved by numerous studies. It is low-cost, non-invasive, easy to use, repeatable, time-saving, applicable by even less-skilled nursing staff, proven to have excellent sensitivity and high specificity. When used in addition to the initial physician's examination before dismissing a newborn home, this postnatal test can increase the clinical accuracy of detecting c/s-CHD. In this sense, it must be used as an early detecting screening test. Its use is more important during the period in which the patent ductus arteriosus (PDA) conceals the signs and symptoms of low cardiac output syndrome (LCOs) or severe cyanosis that will lead to notably hypoxia and acidosis. These free-of-symptoms babies that leave maternity units although critically ill, as well as those that are born at home and assessed by primary care, will benefit the most through a compulsory use of this test. Despite the benefits, it has failed to become a universal screening test for early detection of c/s-CHD, especially in Europe. Aim: To discuss the existing evidence on safe, effective, and efficient screening, using POX in combination with initial pre-discharge physical examination at the end of its stay under maternity services, including births out of medical facilities, for every term baby as a compulsory health screening test in Greece. Methods: The authors, members of the Hellenic Society of Perinatal Medicine (HSPM), reviewed the existing up-to-date literature and the trend of using this test worldwide and especially in European countries. They also consulted with pioneers and experts in the field. Results: Based on published data, the authors clarify existing policies of using POX and initial clinical assessment, aiming to a standardized approach of screening and diagnostic follow-up, when needed. Key issues for future research and evaluation were identified and addressed. Conclusions: The authors clarify existing policies in the use of POX, aiming to suggest the most appropriate way of using the test for compulsory screening term newborns during the early neonatal period in Greece. Special conditions of screening are being discussed. Public health organizations and private health agencies will have an important role in quality assurance and surveillance of this screening test aiming to significantly reduce morbidity and mortality from c/s-CHD in Greece.